Early Intervention with a Parent-Delivered Massage Protocol Directed at Tactile Abnormalities Decreases Severity of Autism and Improves Child-to-Parent Interactions: A Replication Study. (24th March 2015) - Silva, Louisa M. T.; Schalock, Mark; Gabrielsen, Kristen R.; Budden, Sarojini S.; Buenrostro, Martha; Horton, Gretchen
Abstract : Tactile abnormalities are severe and universal in preschool children with autism. They respond well to treatment with a daily massage protocol directed at tactile abnormalities (QST massage for autism). Treatment is based on a model for autism proposing that tactile impairment poses a barrier to development. Two previous randomized controlled trials evaluating five months of massage treatment reported improvement of behavior, social/communication skills, and tactile and other sensory symptoms. This is the first report from a two-year replication study evaluating the protocol in 103 preschool children with autism. Parents gave daily treatment; trained staff gave weekly treatment and parent support. Five-month outcomes replicated earlier studies and showed normalization of receptive language (18%, P = . 03 ), autistic behavior (32%, P = . 006 ), total sensory abnormalities (38%, P = . 0000005 ), tactile abnormalities (49%, P = . 0002 ), and decreased autism severity (medium to large effect size, P = . 008 ). In addition, parents reported improved child-to-parent interactions, bonding, and decreased parenting stress (44%, P = . 00008 ). Early childhood special education programs are tasked with addressing sensory abnormalities and engaging parents in effective home programs. Until now, they have lacked research-based methods to do so. This program fulfills the need. It is recommended to parents and ECSE programs (ages 3–5) at autism diagnosis.